VALIDITY AND JUSTIFIABILITY OF CRIMINALISATION OF DEFAMATION: ANALYSIS OF CERTAIN OBJECTIVE FEATURES OF THE COMPOSITION (CORPUS DELICTI) OF DEFAMATION - Dambrauskienė, Aušra (Teisė, 2015)
While the European Convention for the Protection of Human Rights and Fundamental Freedoms, and the Constitution of the Republic of Lithuania guarantee the right to the defence of personal honour and dignity, it does not specify in which ways and means this right can be exercised. Therefore, the states themselves can choose appropriate remedies in the light of the moral rules established in the society on this matter, the defence priorities, economic conditions, the position of the legislature, and other factors. The choice of the Lithuanian state to defend a person’s honour and dignity in both civil and administrative and criminal legal remedies raises doubts as to its compatibility with the nature and purpose of the criminal law, as well as the principle of criminal liability, as the last resort (ultima ratio), and international commitments. The above doubts are primarily reflected by the absence of the unified conception of the offense of defamation, i.e. the abstract nature, relativity and subjectivity of personal legal goods such as honour and dignity, as well as mismatch between the objective features of the corpus delicti of defamation to the requirements of legal technique, i.e. their evaluative nature. The relation between the personal honour and dignity and freedom of expression too. This complicates the application of criminal liability (criminal law) and poses a threat of unjust prosecution and punishment. Therefore, the criminal law being the strongest remedy of the state, the defence of a person’s honour and dignity in criminal legal means becomes questionable and dangerous both for the individual to whom this remedy is applied, and the general public.